Travels in Alaska - Muir, John, 1838-1914 (Salt Lake City, UT : Project Gutenberg, 2005)
"Travels in Alaska" by John Muir is a travelogue and natural history account written in the late 19th century. The book details Muir's expeditions into Alaska, capturing the majesty of its landscapes, glaciers, and ecosystems, while also exploring his reflections on nature and the human experience in these wild spaces. At the start of the book, Muir sets the stage for his journey to Alaska, describing his previous explorations in California's Sierra Nevada and his eagerness to explore the northern landscapes. He embarks on a voyage through Puget Sound and the Alexander Archipelago, filled with vivid imagery of the ocean, the marine life he encounters, and the lush forests that frame the coastline. Muir's writing captures both the beauty and the challenges of travel, painting a picture of the wild land he is witnessing with a sense of awe and reverence for its natural splendor. He introduces readers to the characters of his journey, including local residents and fellow travelers, and recounts his experiences navigating the unique hazards of exploration in this remote wilderness. (This is an automatically generated summary.)
Release date is 2005-01-01
Harold Wood and Andrew Sly
Keywords: Alaska -- Description and travel; Naturalists -- United States -- Biography; Muir, John, 1838-1914 -- Travel -- Alaska; Conservationists -- United States -- Biography